(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the grammatical structure and semantic characteristics of similes in the Uzbek language. Similes, as a prominent stylistic device, play a crucial role in expressing comparisons, emphasizing qualities, and enhancing the figurative meaning of expressions. The study investigates the syntactic patterns commonly used in Uzbek similes, including noun-based, adjective-based, and verb-based comparisons, and analyzes the morphological markers that signal resemblance. Semantic analysis focuses on how similes convey similarity, intensity, or metaphorical nuances within context. The research highlights the interplay between grammar and meaning in similes, contributing to a deeper understanding of Uzbek stylistics and its application in language teaching, literary analysis, and linguistic research.